Experimental investigation the effect of bamboo micro filler on performance of bamboo-sisal-E-glass fiber-reinforced epoxy matrix hybrid composites - Debela N. Gurmu; Hailemariam M. Gebrelibanos; Chala A. Tefera; Belete Sirahbizu (Heliyon)
The numerous advantages of natural fiber reinforced hybrid composites, such as their light weight, biodegradability, recyclability, availability, and low cost, have brought them to the forefront for various structural applications in the automotive and aerospace industries. Aim of this study was to evaluate the impact of varying the weight fractions of bamboo micro filler on the tensile, flexural, impact, and water absorption properties of the Sisal-Bamboo-E-glass fiber reinforced epoxy matrix hybrid composite prepared by manual hand layup method. To enhance the bond between natural and synthetic fibers and reduce the hydrophilic nature of natural fibers, bamboo and sisal fibers were treated with 5 % NaOH for 6 and 8 h, respectively. The E-glass fiber content was kept constant at 10 %, while the weight fractions of sisal, bamboo fiber, epoxy matrix, and bamboo micro filler were varied. The bamboo micro filler size ranged from 75 to 100 μm. Tensile and flexural tests were conducted using a computer-controlled universal electromechanical testing machine, while impact testing was performed with a Charpy impact test machine. The results showed that the hybrid composite containing 15 % sisal, 10 % glass, 15 % bamboo fiber, 57 % epoxy, and 3 % bamboo micro filler exhibited the highest tensile strength (87 MPa),flexural strength (77 MPa), high impact energy (8.9 J) and high toughness (24.64 J/cm2). Conversely, the highest water absorption capacity was observed in composites with 6 % bamboo micro filler. Overall, the tensile, flexural, impact, and water absorption properties of the hybrid composites were significantly influenced by the weight fractions of the fibers and bamboo micro filler.